Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T13:15:28+01:00
1) = x²+2x+1-2x² =2x+1-x²
2) =-2(9x²-6x+1)+18x²=-18x²+12x-2+18x²=12x-2
3) =3(4a²-1)= 12a²-3
4) =x²-64-x²+8=-56
5) = -(x²-8x+16)+(x²+8x+16)= 16x
6) = 9t²-6t+1-9t²+1=-6t+2
1 5 1
2010-01-24T13:44:49+01:00
A) (x + 1)² -2x² = x² + 1 -2x² = -x² + 1
b) -2(3x - 1)² + 18x² = (-6x + 2)² + 18x² = -6x² + 4 + 18x²= 12x² + 4
c) 3(2a + 1)(2a - 1) = (6a+3)(2a - 1) = 12a² - 6a + 6a -3 = 12a² - 3
d) (x + 8)(x - 8)-(x² - 8) = x² - 8x + 8x -64 - x² + 8 = -56
e) -(x - 4)² + (x + 4)² = -x² + 4² + x² + 4² = 8²
f) (3t - 1)² - (3t + 1)(3t - 1) = 3t² + 1 -(9t² - 3t + 3t -1) = 3t² + 1 - 9t² + 3t - 3t + 1 = -6t² +2
2 5 2